Broad Themes of Difference between French and Americans in Attitudes to Food and Other Life Domains: Personal Versus Communal Values, Quantity Versus Quality, and Comforts Versus Joys - Rozin, Paul; Remick, Abigail K.; Fischler, Claude (Frontiers in Psychology, 2011)
Analysis of previous literature on the role of food in life in France and the United States suggests some fundamental differences in attitudes which may generalize outside of the food domain. Questionnaire results from French and American adults suggest that, compared to the French, Americans emphasize quantity rather than quality in making choices, Americans have a higher preference for variety, and Americans usually prefer comforts (things that make life easier) over joys (unique things that make life interesting). The American preference for quantity over quality is discussed in terms of the American focus on abundance as opposed to the French preference for moderation. The American preference for variety is reflective of Americans’ more personal as opposed to communal food and other values.